The Transformation of Sustainable Community Empowerment Based on Islamic Boarding Schools System - Sudiapermana, Elih; Muslikhah, Muslikhah (Journal of Nonformal Education, 2020)
Community empowerment and education are closely related to advancing society. The purpose of this study was to analyze the implementation and transformation of sustainable community empowerment based on Islamic boarding school system. This is due to the assumption that Islamic boarding school, as a sharia economic developer, gives several impacts on training entrepreneurship, independence of santri, and prosperity of the society. This research used a qualitative method with the phenomenological approach from Edmund Husserl. Phenomenology or transcendental phenomenology aims to find the existence of consciousness essence (intentionality) which consists of four awareness activities. The results of this study indicate that the community empowerment in Al-Ittifaw Islamic boarding school refers to environmental use. The school also adopts an experiential learning and learning by doing system. These systems accustomed the students to learn, maintain, and preserve nature. The agribusiness development of Al-Ittifaq Islamic Boarding School is based on INPEKBI (Divine, Domestic, Personal, Economic, Family, Passion, Ilmihi) principle. The conclusion of this paper is, several stages are needed in terms of raising awareness, habituation, and reinforcement to build the entrepreneurial spirit during the transformation of sustainable community empowerment based on Islamic boarding school system.